Faktor-Faktor Yang Mempengaruhi Pengambilan Keputusan Investasi Saham - Nuryasman MN, Nyoman Suprasta, (Jurnal Ekonomi, 2020)
: Investment decision making is a complex process that includes analysis of several factors and follows various steps. The purpose of this study is to identify factors that influence investment decision making among potential individual investors in Indonesia. Four behavioral factors can influence investment decision making, namely Financial literacy, financial experience, locus of control and experience regret A set of questionnaires were distributed to 420 individual stock investors to measure their investment decisions. The results of this study indicate that financial literacy, locus of control, and financial experience have a positive relationship with their investment decisions, while the Regret experience has a negative relationship with their investment decisions. This study provides information that can help guide future research and help formulate policy-makers as well as educate on the factors that can influence investors' decisions.